THE INFLUENCE OF PERCEIVED SUPERVISOR SUPPORT AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE: (THE MEDIATING ROLE OF JOB SATISFACTION AT PT XYZ) - Salsabila Azzahro; Asep Gunawan; Risdianto Risdianto (Jurnal Maneksi, 2026)
Introduction: Employee performance has become an urgent concern for textile manufacturers in Indonesia as competitive pressures intensify, with this concern centred on three interrelated factors: how supervisors are perceived to support staff, how engaged employees feel, and how satisfied they are with their jobs. However, the psychological chain linking these factors has not received adequate empirical attention—particularly the role of job satisfaction as a bridge between them.Methods: A quantitative approach was adopted, utilising survey responses from 278 employees at PT XYZ who had a minimum of two years of service and were chosen purposively from a total workforce of 1,202. The study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate the proposed conceptual framework.Result: When supervisor support and employee engagement are present together, there is a notable rise in job satisfaction. This heightened satisfaction is the main pathway through which supervisor support and engagement enhance employee performance. Findings from this study confirm that all three variables—supervisor support, engagement, and satisfaction—exert a meaningful and substantial influence on how well employees perform in their roles.Concluding remarks and recommendations: The findings suggest that increasing supervisor support, fostering greater employee engagement, and improving job satisfaction are key strategies for boosting employee performance. Future studies are encouraged to examine additional organisational and psychological factors or use longitudinal research designs to gain deeper insights into employee performance, particularly in labour-intensive industries. Keywords: Employee engagement, Employee performance, Job satisfaction, Perceived supervisor support, PLS-SEM